An Improved Stochastic Model for the Geodetic GNSS Receivers Under Ionospheric Scintillation at Low Latitudes - Xiaomin Luo; Yingzong Lin; Xiaolei Dai; Shaofeng Bian; Dezhong Chen (Space Weather)
Abstract The receiver tracking error stochastic (RTES) model can improve GNSS precise point positioning (PPP) performance under ionospheric scintillation. However, it relies on scintillation products derived from ionospheric scintillation monitoring receivers (ISMRs), which means the RTES model cannot be used for abundant geodetic GNSS receivers. In this study, we propose an improved RTES, referred to as Impr_RTES model, to mitigate scintillation effects on geodetic GNSS receivers at low latitudes, where severe scintillation frequently occurs. In the Impr_RTES model, the tracking error variances at the output of code delay locked loop are calculated by using the index S4c, and these of phase locked loop are modeled by using the rate of total electron content index (ROTI) and S4c. Both S4c and ROTI can be derived from geodetic GNSS receivers. The performance of the Impr_RTES model is validated by using the data sets from ISMR and geodetic receivers, respectively. Using one month of GPS data collected at HNLW station installed with ISMR in Hainan of China from 1 to 28 February in 2023, statistical results indicate that the PPP solution based on Impr_RTES model can improve the positioning accuracy by approximately 22.6%, 23.8%, and 30.2% in the east, north, and up directions, respectively, over the elevation angle stochastic (EAS) model. Meanwhile, the positioning performance of Impr_RTES PPP is comparable to that of RTES PPP. For the GPS data from geodetic receivers, experimental results suggest that compared with EAS, the Impr_RTES model can obviously mitigate scintillation effects on PPP.